Dinámica y estructura de la población de chiguiros (hydrochaeris hydrochaeris : rodentia hydrochaeridae) de Caño Limón, Arauca, Colombia. - Aldana Domínguez, Juanita (Universidad Nacional de Colombia, 2018)
Limón-Limón ácido- Citrus limonum Risso